2018
DOI: 10.4236/ojg.2018.87040
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Threshold Analysis and Bayesian Probability Method for Landslide Initiation Based on Landslides and Rainfall Events in the Past

Abstract: In this paper a rainfall threshold and a Bayesian probability model are presented for the landslide occurrence of shallow landslides in Ha Giang city and the surroundings, Vietnam. The model requires the data on daily rainfall combined with the actual dates of landslide occurrences. Careful study on the database is a prerequisite for the paper. For this reason, selecting the input data was carried out carefully to ensure the reliable results of the study. The daily rainfall data covering a time span of 57 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Bayesian results of rainfall conditions for the landslide early warning system Previous studies used a one-dimensional Bayesian model to examine cumulative event rainfall, rainfall duration, rainfall intensity, 14-day antecedent rainfall, and 30-day antecedent rainfall based Graph showing the results of the two-dimensional Bayesian model for different 3-day antecedent rainfall and cumulative event rainfall on the daily rainfall (Berti et al 2012;Robins 2016;Gonzalez and Caetano 2017;Dikshit et al 2018;Do and Yin 2018). In this study, rainfall intensity, the hourly maximum rainfall, and the 3-day antecedent rainfall, which are highly correlated with landslide occurrence, were added to the two-dimensional Bayesian model, while the 30-day antecedent rainfall, which was not highly correlated with landslide occurrence, was excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian results of rainfall conditions for the landslide early warning system Previous studies used a one-dimensional Bayesian model to examine cumulative event rainfall, rainfall duration, rainfall intensity, 14-day antecedent rainfall, and 30-day antecedent rainfall based Graph showing the results of the two-dimensional Bayesian model for different 3-day antecedent rainfall and cumulative event rainfall on the daily rainfall (Berti et al 2012;Robins 2016;Gonzalez and Caetano 2017;Dikshit et al 2018;Do and Yin 2018). In this study, rainfall intensity, the hourly maximum rainfall, and the 3-day antecedent rainfall, which are highly correlated with landslide occurrence, were added to the two-dimensional Bayesian model, while the 30-day antecedent rainfall, which was not highly correlated with landslide occurrence, was excluded.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the use of empirical models, probabilistic model using Bayes' theorem was developed by [14] is an efficient choice and the same was applied to the Emilia-Romagna region in Italy. Thereafter, similar work was carried out in several places (e.g., Ha Giang region, Vietnam [15], Sierra Norte De Puebla, Mexico [16], Kalimpong, India [17,18], Chibo, India [19]. The use of probabilistic techniques has also been carried out for severe precipitation conditions [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian Risk Measurement in banking institutions and the construction industry has been carried out by (Eschmann et al, 2019;Erango and Goshu, 2019;Zhou et al 2018;Do and Yin, 2018;Fong et al, 2017;Kim et al 2012;Kumar, 2010). In addition, Zhou et al (2018) did a risk assessment and showed that the Bayesian network method performs risk assessment effectively and works flexibly with offshore wind power construction.…”
Section: Introductionmentioning
confidence: 99%